The objective structured clinical examination in anaesthesia practice papers for teachers and trainees - Mendonca, Cyprian; Balasubramanian, Shyam (Tfm Pub., 2007)
The Objective Structured Clinical Examination (OSCE) is a highly reliable and valid tool for the evaluation of trainees in anaesthesia. This book contains 100 OSCE stations with answers based on practical procedures, clinical skills, communication skills, data interpretation, anaesthetic equipment and the management of incidents on a simulator.